ANALISIS SISTEM INFORMASI AKUNTANSI PEMBELIAN DAN PENJUALAN PADA BENGKEL AHASS MITRA KARYA MOTOR - Artiara Egita SE (Jurnal Ilmiah Mahasiswa FEB, 2019)
The purpose of this research is to analyze the implementation of the accounting information system of purchasing and selling in Ahass Mitra Karya Motor workshop by utilizing PIECES Analysis Theory. The theory identifies the problems of the accounting information system implemented based on such aspects as performance, information, economy, safety, efficiency and customer service, in which the object is Ahass Mitra Karya Motor workshop. Of six aspects employed to identify the implementation of the accounting information system of purchasing and selling in Ahass Mitra Karya Motor workshop, three (economy, performance, and efficiency) are considered to meet the standard of PIECES theory; whilst the others (information, safety, and customer service) are considered fail to meet the standard. Keywords: accounting information system, purchasing, selling